Clinical Feasibility and Safety of Scleral Collagen Cross-Linking by Riboflavin and Ultraviolet A in Pathological Myopia Blindness: A Pilot Study - Yu Li; Yue Qi; Mingshen Sun; Changbin Zhai; Wenbin Wei; Fengju Zhang (Ophthalmology and Therapy, 2022)
Abstract Introduction To investigate the feasibility and safety of scleral ultraviolet A (UVA) cross-linking (scleral CXL) on pathologically blindness. Methods This was a prospective, observational clinical study. Five patients with monocular blindness due to pathological myopic maculopathy were enrolled. Eyes with best corrected visual acuity (BCVA) under 0.05 were defined as experimental eyes. The fellow eyes were defined as control eyes. Patients first underwent posterior scleral reinforcement (PSR) surgery in the control eye. Thereafter, scleral CXL surgery was performed in the experimental eye on the same day. Visual acuity, BCVA, slit lamp biomicroscopic examination, intraocular pressure measurement, corneal specula microscopies, axis length measurement, funduscopy with pupil dilation, color fundus photography, full-field flash electroretinography, optical coherence tomography, and color Doppler flow imaging were performed at baseline, 1 week, 1 month, 3 months, 6 months, and 12 months after surgery. Results No signs of inflammation were observed after operation and throughout the follow-up period. Retinoschisis was improved, while choroidal neovascularization fibrosis and retinal and choroidal atrophy were unchanged after scleral CXL. There were no statistically significant differences in the ophthalmic artery, central retinal artery, and posterior ciliary artery parameters of color Doppler flow imaging or in retinal thickness, within experimental and control eyes, at baseline, 1 week, 1 month, 3 months, or 12 months (P > 0.05). Conclusions This pilot study verified the feasibility and safety of scleral CXL on human blindness. The UVA-CXL on the sclera of human eyes seems to have the same effect as PSR in preventing progressive pathological myopia in the future. Trial Registration Chinese Clinical Trial Registry (ChiCTR2100042422).